UZBEKISTAN - LAND OF RICH CULTURAL HERITAGE - Teshaboyeva , Nafisa; Suyarboyeva , Yulduz (Effective scientific journals, 2025)
Uzbekistan is a country with a rich cultural heritage, whose history spans several millennia. It is home to ancient cities, historical monuments, architectural landmarks, and archaeological sites. Traditional crafts such as embroidery, carpet weaving, and pottery are still preserved and actively practiced. The music and dance culture of Uzbekistan reflects the diversity and richness of its cultural life. National cuisine, public holidays, and religious ceremonies are also integral parts of the cultural identity of the country. Uzbekistan’s cultural heritage serves as an important source for tourism, academic research, and international relations.